Parent And Teacher Collaboration in Building Readiness of Early Childhood Learning For Next Education Grade - Katoningsih, Sri (Early Childhood Research Journal (ECRJ), 2021)
The transition period in preparing for the next level of schooling needs attention from parents and teachers, especially the preparation for Early Childhood Education (PAUD) to Elementary School (SD), is currently the focus of attention of students, parents, schools and stakeholders’ other education. In preparing for the transition period in the implementation of early childhood education, at least three preparations are needed when entering elementary school, namely ready for children, ready for parents, and ready for school. This study uses a qualitative method. Data collection in this study was carried out through observation, interviews and psychological testing to obtain the truth of empirical data. Through the empirical data collected, it is believed that it will be able to provide answers to the problems in this research. This research was conducted in PAUD in Karanganyar Regency. The data analysis technique uses source triangulation. The results of this study indicate that schools must have educators and education personnel who are professional, responsible, committed teachers, teachers who master the material and teachers who recognize the characteristics of children. Of the five characteristics of teachers that are mandatory to have so that they can help prepare PAUD children to transition to elementary school. The program of activities must also be of high quality, attractive, using a curriculum according to the local cultural context, relevant to interests, ages, needs and unique abilities in enhancing children's development. Schools and teachers need to explore basic concepts in developing curricula to designing appropriate daily learning activities for early childhood. This is also related to the increasing awareness of the importance of developing children's development at the next school level.